ANALISIS TINGKAT PEMAHAMAN GURU TERHADAP PERKEMBANGAN ANAK USIA DINI PADA TAMAN KANAK-KANAK DI KOTA PONTIANAK - Maulidia, Melia; Yuniarni, Desni; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe level of understanding of kindergarten teachers towards development is needed as a provision in the success of the assessment carried out. Therefore, researchers want to know more about the level of teacher understanding of early childhood development in Pontianak City. The focus of the problem in this study is how the level of teacher understanding of early childhood development in kindergartens in Pontianak City. The purpose of this study was to display data on the level of teacher understanding of early childhood development in kindergartens in Pontianak City. The method used in this research is descriptive method. The approach in this study uses a quantitative approach and is explained descriptively. While the data collection techniques are documentation and measurement test questions. The data analysis technique used in this research is the formula of the central tense of Mean, Mode, and Standard Deviation. Based on the results of data analysis shows that the level of understanding the development of religious and moral values is good. With a total of 76.04% of respondents. Level of Understanding Motor physical development is good, with a number of 55.21% of respondents. The level of Cognitive Understanding is good, with a number of 84.35% of respondents. 38% of respondents. The level of understanding of social and emotional development is good with a number of 42.71% of respondents. The level of understanding of the development of art is good with a total of 48.96% of respondents.Â Keywords: Level of understanding of early childhood development